Simulation of a System of Lowland Sheep Production with Different Times of Lambing - EDELSTEN, P. R.; NEWTON, J. E. (The Libyan Journal of Agriculture, 2023)
A simulation model of a flock of Masham sheep rotationally grazing a sward of S24 perennial ryegrass in England was used to show the economic differences between three times of lambing. Under U.K. prices for 1976. early-lambing was most profitable overall since the lambs could be fattened quickly on the spring flush of grass and sold early at a higher price. Late-lambing was most profitable only if a catch crop of stubble turnips was used to fatten lambs in October to December, and the lambs sold at a high price in late December. Year-to-year variations in gross margin due to variations in herbage production were lowest in the early lambing system since year-to-year variation in herbage production is lowest in the first half of the year.